2013
DOI: 10.3390/ma6072701
|View full text |Cite
|
Sign up to set email alerts
|

Millimeter Wave Radiations Affect Membrane Hydration in Phosphatidylcholine Vesicles

Abstract: A clear understanding of the response of biological systems to millimeter waves exposure is of increasing interest for the scientific community due to the recent convincing use of these radiations in the ultrafast wireless communications. Here we report a deuterium nuclear magnetic resonance spectroscopy (2H-NMR) investigation on the effects of millimeter waves in the 53–78 GHz range on phosphocholine bio-mimetic membranes. Millimeter waves significantly affect the polar interface of the membrane causing a dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 26 publications
2
8
0
Order By: Relevance
“…It was concluded that MMW radiation causes an increase in membrane permeability, dependent on bilayer curvature and a possible role of water molecules bound to the functional groups of lipids in the glycerol region. This conclusion is consistent with studies by Beneduci et al [ 69 , 83 , 84 ], where the multilamellar vesicles (phosphocholine based) were exposed to a wide-band and various monochromatic MMW radiation (53.37, 62.10, 65 GHz) of low power density (0.0035–0.01 mW cm −2 ) for up to 4 h. It was shown that MMW induces the reduction in the water ordering in the nearest proximity to the membrane surface in time- and hydration-dependent manner. The authors also pointed on accumulation phenomena during the exposure and that absorbed electromagnetic energy stored in the form of chemical potential but not thermalized [ 69 ].…”
Section: Biological Effects Of Millimetre Wavesupporting
confidence: 94%
See 2 more Smart Citations
“…It was concluded that MMW radiation causes an increase in membrane permeability, dependent on bilayer curvature and a possible role of water molecules bound to the functional groups of lipids in the glycerol region. This conclusion is consistent with studies by Beneduci et al [ 69 , 83 , 84 ], where the multilamellar vesicles (phosphocholine based) were exposed to a wide-band and various monochromatic MMW radiation (53.37, 62.10, 65 GHz) of low power density (0.0035–0.01 mW cm −2 ) for up to 4 h. It was shown that MMW induces the reduction in the water ordering in the nearest proximity to the membrane surface in time- and hydration-dependent manner. The authors also pointed on accumulation phenomena during the exposure and that absorbed electromagnetic energy stored in the form of chemical potential but not thermalized [ 69 ].…”
Section: Biological Effects Of Millimetre Wavesupporting
confidence: 94%
“…This conclusion is consistent with studies by Beneduci et al [ 69 , 83 , 84 ], where the multilamellar vesicles (phosphocholine based) were exposed to a wide-band and various monochromatic MMW radiation (53.37, 62.10, 65 GHz) of low power density (0.0035–0.01 mW cm −2 ) for up to 4 h. It was shown that MMW induces the reduction in the water ordering in the nearest proximity to the membrane surface in time- and hydration-dependent manner. The authors also pointed on accumulation phenomena during the exposure and that absorbed electromagnetic energy stored in the form of chemical potential but not thermalized [ 69 ]. This agrees with another study conducted on mixed phospholipid monolayer exposed for up to 5 h to 60 GHz, 0.009–0.9 mW cm −2 , showing a significant increase in lipid monolayer lateral pressure upon MMW application [ 85 ].…”
Section: Biological Effects Of Millimetre Wavesupporting
confidence: 94%
See 1 more Smart Citation
“…We propose two (potentially interconnected) consequences of the MMW-induced disorientation of the water dipoles at the hydration layer of the neuronal plasma membrane before their rotational energy is thermalized and dissipated throughout the tissue: 1 ) altered fluidity and/or structure of the transmembrane phospholipids ( Beneduci 2008 ; Davidson et al 2013 ; Ramundo-Orlando 2010 ) via an efficient energy transfer from the hydration layer to the membrane phospholipids ( Mashaghi et al 2012 ); and 2 ) reduced gigahertz-range dielectric permittivity and capacitance of the plasma membrane ( Blum and Henderson 1981 ; Grodsky 1976 ; Sheppard et al 2008 ). Initial support for these hypotheses comes from a theoretical model describing the interaction of MMWs with biological membranes ( Beneduci et al 2014 ) and from experimental studies on biomembranes ( Beneduci et al 2012 , 2013 ; Cosentino et al 2013 ). We hope to evaluate these proposed mechanisms for the observed MMW effects on neuronal activity in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies investigated membrane phase transitions involving exposure to a range of phospholipid vesicles prepared to mimic biological cell membranes. One group of studies by an Italian research group reported effects on membrane hydration dynamics and phase transition [89][90][91]. Observations included transition delays from the gel to liquid phase or vice versa when compared with sham exposures maintained at the same temperature; the effect was reversed after exposure.…”
Section: Membrane Effectsmentioning
confidence: 99%